Rezeptionsgeschichte of Schleiermacher’s religious and theological thought in the Chinese-speaking World - Zhang, Yuntao (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2025)
The religious and theological thought of Schleiermacher, the "father of modern Protestant theology," has been accepted and interpreted by the Chinese-speaking world for more than a hundred years. During this period, China’s political system, social ideology and way of life have undergone great changes, which have greatly influenced and shaped the reception and interpretations of his ideas. Therefore, these interpretations present their own characteristics in different eras and regions. This article takes time as the vertical axis and region as the horizontal axis, and examines the reception and interpretations of Schleiermacher’s religious and theological thought in different periods in Chinese Mainland and Hong Kong and Taiwan districts, presenting their respective representative research results and contributions, depicting their characteristics, and pointing out some of the latest trends worthy of attention.